2005
DOI: 10.1111/j.1572-0241.2005.50018.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases Expression Correlates with Survival in Patients with Esophageal Squamous Cell Carcinoma

Abstract: MMP9 expression is a negative, independent prognostic factor in ESCC and correlates with tumor cell differentiation, vessel permeation, and lymph node metastasis. MMP7, MMP9, and MMP13 may function in early stage ESCC, and their co-expression predicts poor outcome for relatively early stage ESCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 25 publications
8
63
0
2
Order By: Relevance
“…Houldsworth et al (27) identified an association between MET and EC, while Gu et al (28) showed that MMP9 affected the survival of patients with this disease. PDGFA was detected in EC by Wong et al (29) and Aoki et al (30) suggested that SERPINE1 may be a potentially important index for the prediction of post-operative illness.…”
Section: Discussionmentioning
confidence: 99%
“…Houldsworth et al (27) identified an association between MET and EC, while Gu et al (28) showed that MMP9 affected the survival of patients with this disease. PDGFA was detected in EC by Wong et al (29) and Aoki et al (30) suggested that SERPINE1 may be a potentially important index for the prediction of post-operative illness.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 and MMP-9 activation has been proposed to be critical for carcinoma progression since the proteolytic ability of type IV collagen is associated with cancer metastatic ability (Liotta et al 1980(Liotta et al , 1991. Several reports have indicated that MMPs are associated with the malignant potential of esophageal cancer (Koyama et al 2000;Polette et al 2004;Samantaray et al 2004;Gu et al 2005). Interestingly, Kim et al (1998) demonstrated that MMP-9 activity, and not MMP-2 activity, could significantly affect tumor intravasation into blood vessels by degrading the basement membrane.…”
Section: The Combination Of Egfr Overexpression Htert Activation Anmentioning
confidence: 99%
“…The first step of tumor development and metastasis is the proteolysis of microvessel basement membranes and invasion of endothelium. The migration of tumor cells is associated with the degradation of the extracellular matrix (ECM) [19]. The ECM is a dynamic structure composed of various macromolecules such as collagen, fibronectin, laminin and proteoglycans of connective tissue.…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%